INTERNALISASI NILAI KARAKTER BERBASIS DAQU METHOD PADA PESERTA DIDIK DI LINGKUNGAN SEKOLAH - Zubaidi; Zukhruful Irbah (Indonesian Society and Religion Research, 2025)
This study examines the impact of the Daqu Method on students in Daarul Qur'an Indonesia Elementary School. The method includes seven pillars: congregational prayer, heart and attitude guarding, Tahajud, dhuha, qobliyah, and ba'diyah; memorizing and contemplating the Qur'an; alms and Sunnah fasting; learning and teaching; prayer and prayer requests. This study uses a literature review strategy or library study, where the author collects relevant articles, journals, books, and papers and interprets them into one study. This study shows that instilling religious values through the Daqu Method in elementary education affects students' personalities, inspiring them with religious, social, and noble values. In addition to the above impacts, students exhibit empathy compassion, and want to serve others. They theoretically and practically grasp the Daqu method's character principles daily. Daqu Method, Character Values, Students, Schools